SYNTHETIC AND ANTIMICROBIAL ACTIVITY OF 4 THIAZOLIDINONES - Dixit, Renu; Halve, A. K.; Shinde, C. P.; Soni, Pradeep K. (International Journal of Current Pharmaceutical Research, 2015)
Objective: Thiazolidinone, a saturated form of thiazole with carbonyl group on the fourth carbon, has been considered as magic moieties (Wonder nucleus) which possess almost all types of biological activities. This diversity in the biological response profile has attracted the attention of many researchers to explore this skeleton to its multiple potential against several activities Methods: Looking to the importance of N and S hetero cycles in the medical field, 4-thiazolidinone derivatives (3b,4b) have been synthesized by cyclization of substituted imines(1a,2a) with mercaptoacetic acid in presence of anhydrous ZnCl2 as a catalyst in DMF. The 4-thiazolidinone derivatives have also been tested against two bacterial strains viz. S. aureus and E. coli and two fungal pathogens viz. A. niger and C. albicans using Kirby-Bauer method. Result: New series of azomethines and 4 thiazolidinones compounds have been prepared. The synthesized compounds were characterized on the basis of IR, 1H-NMR, and elemental analysis. The purity of the compounds was checked using pre coated TLC plates (MERCK) using n-hexane: ethyl acetate (8:2) solvent system. The synthesized compounds show good antimicrobial acivity. Conclusion: The zone of inhibition is directly proportional to the degree of sensitivity of the bacterial, fungal strain and concentration of compound under test. A systematic perusal data of antimicrobial activity reveals that, with the increase in concentration of drug, increase in zone of inhibition occur in petridish. Better antimicrobial activity have been pointed out in synthesized compounds.